Is islam a religion of moderation or extremism? a study of key islamic teachings - Ushama, Thameem (Canadian Center of Science and Education, 2014)
This article strives to present a brief analysis of Islamic religious sources and examines whether the claim that Islam is immoderate is true or false, especially in relation to the method of moderation applied in religious teachings, requirements and human relations and substantiates that it is a religion of flexibility, goodness, ease, moderation and not extremism. It employs content analysis of relevant verses of the Scripture and statements of the Prophet that refer to the method of moderation and explanations of selected Qur'ānic exegetes. It focuses on understanding the concept of moderation and explains important terms (1) Excessiveness or Extremism, (2) Laxity, Negligence or Harshness and (3) Straight Path that lead to understand the proper meaning of moderation. It also explores its most significant features such as (1) Excellence or Goodness, (2) Justice, (3) Ease and Removal of Hardship, (4) Wisdom (5) Straightness and (6) Between Two Things and lastly it provides the conclusion and recommendations.